Development of robust H∞ control for active suspension of half car model with genetic algorithm tuning - Kaleemullah, Mohammed (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Better ride comfort and controllability of vehicles are pursued by automotive industries by considering the use of suspension system which plays a very important role in handling and ride comfort characteristics. Comprehensive comparison on half car model was conducted to analyze the effect of active suspension system, namely, Robust H-infinity and LQR controller on the model. Passive suspension system is also compared with active suspension technique for the purpose of benchmarking. Parametric uncertainties were also considered to model the non-linearities associated in the system. Sprung mass vertical acceleration and pitch acceleration responses were analyzed for measurements of ride quality and road handling. Suspension deflection and tire deflection responses were analyzed to identify any compromise in other aspects of vehicle dynamics. Results show that the Robust and LQR controller successfully controlled the active suspension, improving both the ride quality and handling of the vehicles without compromising the rattle-space requirement and road holding performance of the vehicles. Comparison of all models also shows that in spite of adding uncertainties in the system, the designed Robust H-infinity controller achieved better settling time than the traditional passive suspension system.